Effect of Earnings Per Share (EPS), Price to Earnings Ratio (PER), Market to Book Ratio (MBR), Debt to Equity Ratio (DER), Interest Rate and Market Value Added (MVA) on stock prices at commercial banks registered in 2016-2019 Indonesia Stock Exchange - Amiputra, Satria; Kurniasari, Florentina; Ade Suyono, Kristianus (ADI Publisher, 2021)
This research was conducted by using the object of research, 7 banks listed on the Indonesia Stock Exchange. The independent variable in this study is earnings per share (EPS), price earnings ratio (per), market to book ratio (MBR), debt to equity ratio (DER), interest rate (int) and Market Value Added (MVA). While the dependent variable in this study is the stock price (market price). The results of this study are earnings per share (EPS), price earnings ratio (per), and the Market to Book Ratio (MBR) have a positive effect on stock prices. While the Debt to Equity Ratio (DER), Interest Rate (INT), and Market Value Added (MVA) have a negative effect on stock prices. Earnings Per Share (EPS), Price Earnings Ratio (PER), Market to Book Ratio (MBR), Debt to Equity Ratio (DER), Interest Rate (INT), and Market Value Added (MVA) together influence and significantly against stock prices.